Analogies Used in a General Biology Course: How is DNA Conserved Across Generations? - Nazlı Rüya Taşkın Bedizel; Nursen Azizoğlu (Universitas Pendidikan Indonesia, 2023)
The present study has two main goals. First, it aims to examine the analogies an instructor uses about